Design of community based breeding programs for two indigenous goat breeds of Ethiopia - Abegaz, Solomon (University of Natural Resources and Life Sciences, Vienna, 2014)
The objectives of this study were to describe the production systems, identify the breeding objectives traits, describe the morphological and molecular characteristics of Western Lowland and Abergelle goat breeds of Ethiopia to design community based breeding programs. 120 goat keepers were interviewed. Phenotypic characters of 534 Abergelle and 476 Western Lowland goats were measured. Genetic diversity of the two Ethiopian and three Nigerian goat types were assessed based on 47K Single Nucleotide Polymorphism markers. The breeding objective traits were investigated through own and group animals ranking experiments. Community based one tier breeding schemes with four different alternatives for the top three most important traits were simulated. The survey results indicated that goats were kept for multifunctional roles in both areas. Phenotypic characterization showed high variability within and between the studied breeds in qualitative and quantitative traits. Western Lowland goats are on an average not only bigger than Abergelle goats but also show considerably higher variation in body size. The genetic diversity analysis revealed that the studied goat populations were well differentiated based on their geographical location. Production and reproduction traits such as body size, twinning and milk yield were identified as important breeding objective traits in own flock ranking experiment while in group ranking experiment the observable characters like body size, body conformation and coat color were identified as breeding goal traits. Simulation results gave an acceptable range of genetic gains with little difference across the alternatives. Thus, the community based breeding programs with a few traits in the recording are considered feasible for genetic improvement of goats in the study areas and similar agro-ecological zones.